The method for image retrieval based on multi-factors correlation utilizing block truncation coding - Wang, Xingyuan; Wang, Zongyu (Pattern recognition, 2014)
In this paper, we proposed multi-factors correlation (MFC) to describe the image, structure element correlation (SEC), gradient value correlation (GVC) and gradient direction correlation (GDC). At first, the RGB color space image is converted to a bitmap image and a mean color component image utilizing the block truncation coding (BTC). Then, three correlations will be used to extract the image feature. The structure elements can effectively represent the bitmap which is generated by BTC, and SEC can effectively denote the bitmap׳s structure and the correlation of the block in the bitmap. GVC and GDC can effectively denote the gradient relation, which is computed by a mean color component image. Formed by SEC, GVC and GDC, the image feature vectors can effectively represent the image. In the end, the results demonstrate that the method has better performance than other image retrieval methods in the experiment. •Multi-factors correlation (MFC) is used to describe the image.•We utilize the block truncation coding to convert the color image to bitmap.•Structure elements are used to represent the bitmap.•Gradient value correlation is used to denote the gradient relation.•Gradient direction correlation is used to denote the gradient relation.